2019
DOI: 10.3390/nu11020416
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Caffeine and Coffee on Human Health

Abstract: Coffee is one of the most widely consumed beverages in the world and is also a major source of caffeine for most populations [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
3
40
0
9
Order By: Relevance
“…Caffeine (CAF) is one of the most consumed beverages globally, second only to water, and it is present in coffee, tea, and soft drinks. 1 Coffee is a principal route of exposure to CAF in the European population, while tea constitutes the main route of CAF in Asian communities. 2 It has been reported that regular coffee consumption lowers the risk of type II diabetes and reduces the risk of impaired glucose tolerance due to its anti-inflammatory and antioxidant effects, and modulation of adenosine receptor signaling and microbiome content.…”
mentioning
confidence: 99%
“…Caffeine (CAF) is one of the most consumed beverages globally, second only to water, and it is present in coffee, tea, and soft drinks. 1 Coffee is a principal route of exposure to CAF in the European population, while tea constitutes the main route of CAF in Asian communities. 2 It has been reported that regular coffee consumption lowers the risk of type II diabetes and reduces the risk of impaired glucose tolerance due to its anti-inflammatory and antioxidant effects, and modulation of adenosine receptor signaling and microbiome content.…”
mentioning
confidence: 99%
“…Overall, the trend that emerges from the various clinical studies is that moderate caffeine intake is generally considered to exert no or even positive effects on human health, with some caveats. That is, despite the observations that daily caffeine intake of up to 400 mg/day for the healthy adult population is not associated with adverse cardiovascular health, behavior, cancer risk, male fertility, calcium homeostasis, and bone health, 14 the nonuniformity of caffeine sources in the various studies makes the interpretation of results difficult, since most caffeinated products contain other compounds that can influence disease risk.…”
mentioning
confidence: 99%
“…effects that often occur due to caffeine intake include palpitations, insomnia, headaches, tremors, anxiety, seizures, arrhythmias, nausea, and vomiting. Besides, the consumption of regular caffeine, especially in large quantities, can cause dependency effects (Cornelis, 2019;Wassef et al, 2017).…”
Section: Determination Of Caffeine Concentrationmentioning
confidence: 99%